2019
DOI: 10.1007/s00425-019-03139-w
|View full text |Cite
|
Sign up to set email alerts
|

Methylobacterium oryzae CBMB20 influences photosynthetic traits, volatile emission and ethylene metabolism in Oryza sativa genotypes grown in salt stress conditions

Abstract: The objective of this study was to analyze the impact of ACC (1-aminocyclopropane-1carboxylate) deaminase producing Methylobacterium oryzae CBMB20 in acclimation of plant to salt stress by controlling photosynthetic characteristics and volatile emission in salt-sensitive (IR29) and moderately salt resistant (FL478) rice (Oryza sativa L.) cultivars. Saline levels of 50 mM and 100 mM NaCl with and without bacteria inoculation were applied, and the temporal changes in stress response and salinity resistance were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 103 publications
(140 reference statements)
2
24
0
Order By: Relevance
“…Methylobacterium oryzae CBMB20 has been well documented in enhancing plant growth under salt‐stress conditions through various mechanisms (Madhaiyan et al ., 2007; Chanratana et al ., 2019; Chatterjee et al ., 2019). To determine the GO‐based clustering in rice inoculated with M .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Methylobacterium oryzae CBMB20 has been well documented in enhancing plant growth under salt‐stress conditions through various mechanisms (Madhaiyan et al ., 2007; Chanratana et al ., 2019; Chatterjee et al ., 2019). To determine the GO‐based clustering in rice inoculated with M .…”
Section: Resultsmentioning
confidence: 99%
“…The differential regulation of the specific proteins important for attaining tolerance against salt stress identified in this study has also been reported previously (Singh et al ., 2017; Zhao et al ., 2021). Likewise, in this study, the abundance of V‐ATPase (Q6EUQ9), which are important proteins for compartmentalizing Na + ions into the vacuole under salt‐stress conditions were increased corroborating previous reports on the V‐ATPase activity enhancement by ACC deaminase producing bacteria (Chatterjee et al ., 2018, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…However, the ACO1 expression was significantly lower in heat-stressed plants inoculated with B. linens RS16 than the non-inoculated ones: 0.8-fold decrease at 40 C and 0.7-fold decrease at 45 C. The decrease in ACO1 expression can be attributed to the ability of B linens RS16 to produce ACC deaminase, which can scavenge the precursor of ethylene, ACC, and converts it into α-ketobutyrate and ammonia (Glick 2014;Madhaiyan et al 2006). The modulation of ACC oxidase activity under different environmental stress conditions by ACC deaminase-producing endophytic bacteria has already been reported (Chatterjee et al 2019;Yim et al 2014).…”
Section: Brevibacterium Linens Rs16 Decreased Ethylene Emission Level...mentioning
confidence: 94%
“…M. nodulans Crotalaria providing nitrogen; decreasing levels of ethylene [12,16,17] M. oryzae Rice increasing plant cytokinin levels; solubilizing phosphate [13,[18][19][20] M. extorquens Pine; Arabidopsis; Brassia inducing the expression of host defense genes [21,22] M. mesophilicum Sugarcane increasing plant cytokinin levels [23] M. radiotolerans Brassia; Combretaceae providing nitrogen; exhibited high antibacterial and antifungal activity; decreasing levels of ethylene [24,25] M. populi Brassia providing nitrogen [26] M. komagatae Brassia providing nitrogen [17] M. aquaticum Brassia providing nitrogen [17] M. funariae Moss increasing plant cytokinin levels [27] M. phyllosphaerae Rice decreasing levels of ethylene [28]…”
Section: Species Name Host Plants Effects On Host Plantsmentioning
confidence: 99%